Role of Lean Six Sigma in the Indian MSMEs during COVID-19. Issue 4 (8th June 2021) - Mishra, Mrigendra Nath; Mohan, Ashutosh; Sarkar, Arghya
Abstract : Purpose: The purpose of this study is to explore the advantages and obstacles of implementing Lean Six Sigma in Indian MSMEs during or post-COVID-19. The following research also elaborates on the challenges of implementing Lean Six Sigma in MSMEs in India, along with the changes in the culture that are required for providing a proper climate to ensure success in a long-term manner. Design/methodology/approach: The methodology used in this study is a descriptive study, which explores and looks for the factors that influence the impulse or motivation to implement Lean Six Sigma in MSMEs and factors that inhibit the implementation of Lean Six Sigma. To achieve this goal of Lean Six Sigma, a significant review of the existing literature of the subject area has been done to prepare a framework with the help of inferential statistics in view of the critical success factors. This research is a flow and arranged a type of survey of organizations that is conducted using MS-Excel and SPSS 25.0 statistical software. The number of participants selected using a purposive sampling method in this study was 127 Lean Six Sigma experts and owners or CEOs of MSMEs in India. Findings: Lean Six Sigma be used for facilitating the improvement processes in manufacturing operations, quality improvements and productivity. As some obstacles exist in implementing the Lean Six Sigma approach, the improvement processes and outcomes of change in the culture are noteworthy and worthwhile. The implementation of Lean Six Sigma has also some constraints, including cost limitations, skill limitations, limited facilities and other such limitations. The implementation of Lean Six Sigma during COVID-19 is not yet a matter of urgency or priority, and hence, cannot yet be applied. Research limitations/implications: This paper presents opinions of only a few selected professionals of Indian MSMEs. So it was a crucial aspect of capturing the views of such practitioners of their arrival on valid and sound conclusions. Practical implications: The novelty of this research is to analyze the advantages and obstacles of implementing Lean Six Sigma in MSMEs during the COVID-19 in India. The results of this research can be used as scientific references for researchers who will conduct future research. Moreover, it can be guidance for MSMEs owners to make decisions in implementing Lean Six Sigma during the COVID-19 pandemic. The organizations assess all of their aspects such as perceive objectives, required qualities and shortcomings for fruitful implementation of any practice. Originality/value: Several suggestions were made for the methods and thoughts, which will constitute a Lean Six Sigma organization. Hence, the research offers an excellent framework for both working professionals and academicians to understand the view of Indian MSMEs along with their benefits and obstacles of implementing Lean Six Sigma. So this study helps in laying out a platform for understanding the uses of Lean Six Sigma for process excellence in a new era due to COVID-19.